Cohort Study of Intracameral Moxifloxacin in Postoperative Endophthalmitis Prophylaxis. (January 2014) - Galvis, Virgilio; Tello, Alejandro; Sánchez, Mary Alejandra; Camacho, Paul Anthony
We conducted a cohort study to evaluate post-cataract surgery endophthalmitis rates in relation to prophylactic intracameral moxifloxacin administration. A total of 2332 patients (2674 eyes) who underwent phacoemulsification by a single surgeon from January 2007 through December 2012 were included in the study. A total of 1056 eyes did not receive intracameral prophylactic moxifloxacin and the antibiotic was injected in 1618 eyes. The incidence of presumed postoperative endophthalmitis in the 2 groups was calculated. The rate of presumed infectious endophthalmitis after cataract surgery between January 2007 and June 2009 (without intracameral moxifloxacin) was 0.094%. The rate in the second period, from July 2009 to December 2012 (with prophylactic intracameral moxifloxacin), was 0%. In our patients, a decline in the incidence of presumed infectious postoperative endophthalmitis appeared to be associated with the application of intracameral moxifloxacin.